2023
DOI: 10.1111/ppa.13769
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of Bacillus velezensisSDTB038 and phenamacril on Fusarium crown and root rot of tomato

Abstract: Fusarium crown and root rot (FCRR) is a damaging ailment that can affect tomato production. It is caused by Fusarium oxysporum f. sp. radicis‐lycopersici (FORL). The use of biological agents, in conjunction with fungicides, has become a practical strategy for combating fungal diseases in crops. Lipopeptide extracts from a potential biocontrol strain of Bacillus velezensis (SDTB038) exhibited an inhibitory effect on the mycelial growth of FORL; the EC50 value was 59.95 mg/L, and at a concentration of 256 mg/L t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The enhanced antifungal effect of bacteria from the genus Bacillus, when applied in combination with some synthetic pesticides, has been reported before [31][32][33][34][35]. For example, Peng and co-workers [31] studied a possible synergistic effect of B. subtilis NJ-18 with flutolanil and difenoconazole fungicides.…”
Section: Antifungal Activitymentioning
confidence: 78%
See 2 more Smart Citations
“…The enhanced antifungal effect of bacteria from the genus Bacillus, when applied in combination with some synthetic pesticides, has been reported before [31][32][33][34][35]. For example, Peng and co-workers [31] studied a possible synergistic effect of B. subtilis NJ-18 with flutolanil and difenoconazole fungicides.…”
Section: Antifungal Activitymentioning
confidence: 78%
“…In another study, Liu and co-workers [33] found that the combined application of the biological agent B. subtilis H158 and synthetic fungicide strobilurin demonstrated a stronger inhibitory effect of rice sheath blight compared to strobilurin alone. Similarly, Chen and co-workers [35] showed that lipopeptide extracts from B. velezensis SDTB038, combined with the fungicide phenamacril, exhibited strong synergistic control against F. oxysporum f. sp. radicis-lycopersici, resulting in an 84% reduction in fungal growth.…”
Section: Antifungal Activitymentioning
confidence: 85%
See 1 more Smart Citation